2019
DOI: 10.1016/j.anbehav.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary roads to syntax

Abstract: Syntax is habitually named as what sets human language apart from other communication systems, but how did it evolve? Comparative research on animal behaviour has contributed in important ways, with mainly three sets of data. First, animals have been subjected to artificial grammar tasks, based on the hypothesis that human syntax has evolved through advanced computational capacity. In these

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…Previous work has suggested that Non-AD processing in language may be a novel application of an evolutionarily ancient ability for computing complex spatial, temporal, or social relationships/hierarchies ( 15 , 26 , 42 , 43 ). Our principal finding that the evolutionary origins of Non-AD processing predates the evolution of language provides key support for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has suggested that Non-AD processing in language may be a novel application of an evolutionarily ancient ability for computing complex spatial, temporal, or social relationships/hierarchies ( 15 , 26 , 42 , 43 ). Our principal finding that the evolutionary origins of Non-AD processing predates the evolution of language provides key support for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, such test may bring information on how birds perceive and deal with combinations and shed light on whether it could be considered semantic compositionality in the human sense (Dutour, Léna, et al., 2019). Semantic compositionality (also termed compositional syntax by some authors) occurs when a combination of words has a meaning emerging from its individual parts (each part having its own meaning), and when the order of such parts is important (Engesser & Townsend, 2019; Suzuki et al., 2019; Zuberbühler, 2019). Debates on whether the “I notes followed by D notes” mobbing sequence can approach human compositional syntax have been profuse (Bolhuis et al, 2018a; Bolhuis et al, 2018b; Suzuki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Along the same lines, Dor (2015) describes language as "the instruction of imagination." Zuberbühler (2019) suggests that grammar itself derives from the perceived structure of events and evolved before communicative language itself. This compositional structure is made up of components such as actors, agents, patients, predication, and so on, and marking them with communicative signals.…”
Section: Language As Thoughtmentioning
confidence: 99%